Social prescribing for people living with long-term health conditions: a scoping review - Anna Wilson; Helen Noble; Karen Galway; Julie Doherty (Systematic Reviews)
Abstract Introduction Social prescribing links people to activities and services typically provided by local voluntary and community sectors to address social determinants of health and wellbeing. People living with long-term health conditions are a target population. This relatively new approach is rapidly expanding, and there is varied evidence regarding how social prescribing is being delivered for people living with long-term conditions. This scoping review aims to report on what is known about the approach for these patient populations. Methods Electronic databases MEDLINE, CINAHL, Scopus, Web of Science, and PsycINFO were searched in December 2023, and relevant sources of gray literature in January 2024, with both updated in February 2025. Studies eligible for inclusion included adults (18 +) with long-term conditions engaging with social prescribing in health and community contexts. Studies published in English in any year were included. A data charting template captured key characteristics including reasons for referral, referral pathways, activities and services being utilized, and outcome measures. A descriptive narrative synthesis was conducted, guided by the review questions to explore the current evidence. Results Thirty-seven sources of evidence were included. Diabetes was the most common of 65 conditions identified (n = 23). The presence of a long-term condition was the most frequent reason for referral (n = 30), followed by mental health concerns (n = 15), and social isolation or loneliness (n = 11). Most referrals were made within primary care (n = 33), to a link worker or social prescriber (n = 29), who supported participants to access activities and services including exercise (n = 22), information, support, and advice (n = 19), mental health support (n = 15), social and leisure activities (n = 15) and condition-specific support (n = 14). Wellbeing was the most commonly identified measured outcome (n = 23), with studies utilizing the Warwick Edinburgh Mental Wellbeing Scales (n = 7) and Wellbeing Star (n = 7) most frequently. Conclusions While common factors were identified, there is considerable variation in social prescribing approaches for people living with long-term conditions, reflecting the diversity of needs, availability of community services, and necessity for personalized care. Further research is needed to inform the development of evidence-based practice which addresses the complex needs of diverse patient populations and supports access to a broad range of referral pathways.